Evaluation of seakeeping analysis of a fishing vessel using a wave buoy and onboard motions monitoring device - Maimun, Adi; Yaakob, Omar; Kamal, Md. Ahm; Ng, Chee Wei (2006)
Seakeeping analysis is important in assessing the performance of floating structure in waves. To perform Seakeeping calculations, the wave characteristics as well as the response of the vessel are needed. The analysis normally requires reliable computer programs to calculate response amplitude operator (RAO) and accurate seaway representation. For seaway representation theoretical spectra can be used but it is always preferable to use the measured spectra which can be obtained through full scale measurement. On the other hand theoretical spectra can be used for comparison. This paper presents the results of a full-scale measurement of wave and vessel motions taken from a Malaysian fishing vessel. The vessel operates off the East Coast of Peninsular Malaysia. Wave buoy was used to measure wave data and Vessel Motion Monitoring System (VMMS) was used to measure the vessel motions. They are basically composed of a set of accelerometers gyroscopes and wind sensors. The data processing and analyzing is done using LabVIEW software. Finally, the main analysis of the results obtained is in the form of spectral analysis of wave and vessel motions. From them the RAO can be obtained, which is the key to all Seakeeping analysis.